Population and Microhabitat Characteristic of Homalomena bellula Schott in Mount Slamet, Central Java, Indonesia - YAYAN WAHYU CANDRA KUSUMA; INGGIT PUJI ASTUTI (Society for Indonesian Biodiversity, 2009)
The population and habitat characteristics of Homalomena bellula Schott in Java have received little attention. In this present study, the authors estimated the population density and habitat characteristic of H. bellula in Mount Slamet, Central Java, by means of random samplings of 2 x 2 m2 plots. Two distinct populations were studied at two different altitude levels, i.e. below and above 1000 m asl. We used to suspect that there was a difference in both populations. But our result revealed that these two populations were actually similar in abundance, population density, and dispersion pattern and even in microhabitat characteristics.